Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, Belanja Modal dan Sisa Lebih Pembiayaan Anggaran Terhadap Kinerja Keuangan pada Provinsi di Pulau Sumatera - Aisyah A Zzahra; Henny Yulsiati; Siska Aprianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to “determine the effect of local revenue, balancing funds, capital expenditure and budget financing surplus on financial performance in Provinces on the Island of Sumatra. This study is a quantitative study using secondary data obtained from the official website www.bpk.go.id. The population in this study were 10 Provinces on the Island of Sumatra with a total sample of 50. The selection of this research sample used the saturated sample technique found in Non-Probability Sampling. This study uses descriptive statistical analysis tools, selection of panel data regression models and classical assumption tests with Eviews 12 and Microsoft Excel. Based on the results of the study, it is known that partially Local Revenue and Balancing Funds have a significant effect on Financial Performance. Conversely, Capital Expenditure and Budget Financing Surplus do not affect Financial Performance in Provinces on the Island of Sumatra.”